Comparative Study of OLGA and LedaFlow Models for Mechanistic Predictions of Hydrate Transport Dynamics - Anqi Qu; Luiz F. R. Dalla; Luis E. Zerpa; Thierry Palermo; Khalid Mateen; Annie Fidel-Dufour; Carolyn A. Koh (Energies)
Gas hydrate formation in pipelines transporting multiphase fluids from petroleum reservoirs can lead to the formation of blockages, representing a significant flow assurance challenge. Key issues caused by hydrates include substantial increases in the viscosity of mixed liquid phases and the deposition of hydrates on the pipeline wall. This study compares two existing transient multiphase flow simulators, OLGA and LedaFlow, in terms of their estimation of hydrate formation effects on multiphase flow. Here, we compared in detail the hydrate kinetic models, parameters used, and initial condition setup approaches that influence hydrate formation and affect multiphase flow properties. Based on the comparison between the simulation results, it was found that using both simulators with default setups may not lead to comparable results under certain conditions. Adjusting input parameters, such as the stoichiometric coefficient and hydrate formation enthalpy, is necessary in order to obtain equivalent results. Hydrate modules in both simulators have also been applied to a field case. With appropriate setup, OLGA and LedaFlow produce comparable results during steady-state simulations, which align with field observations. This work provides guidelines for setting up OLGA and LedaFlow simulation models to obtain equivalent results.